Etnography Myth of Tourism Place in the River Batanghari Nine South Sumatra Province - Boby Agus Yusmiono; Maharani Oktavianti; Neta Dian Lestari (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
There are many myths in South Sumatra, especially in isolated areas because communication and transportation are not going well. For example, infrastructure such as roads, bridges, and water and land transportation has been damaged, making it difficult to access the area so that the myth has increased. Myths are also increased because of broken communication, for example the transmitter is tower error (broken). The tower transmitter is difficult to repair because there is no access to the area. The problem in this study is How Ethnography Myths of Tourism Places in the Batang Hari Sembilan River, South Sumatra Province. The research objectives are to find out the myths of tourism places in the Batanghari nine river basin (Watershed) and to make ethnography of the similarities of myths in the watershed (watershed area) of South Sumatra Province. Current photos to visit, such as in the city of Palembang. Apart from the Musi River and Jempatan Ampera there are Kemarau Island, Kuto Besak Fortress, Kapitan Village, Munawar Village, Rakit House and other places. In Muara Duo district, there is the Komereng River, which is a tourist attraction, namely the Teluk Rasau Lake and the Varaam Village tourist attraction. Lahat Regency has potential tourism objects such as Ayek Lematang Park, Benteng Bridge and Pelancung Ulak Pandan / Gunung Jempol.